The gluon jet function at two-loop order - Becher, T; Bell, G (2011)
The inclusive gluon jet function is evaluated at two-loop accuracy. This function is relevant for resummations of large perturbative logarithms in collider processes involving low-mass gluon jets. The jet function corresponds to the imaginary part of the gluon propagator in light-cone gauge, which is adopted for the calculation. In addition to the leading jet function, the power-suppressed two-gluon jet functions are given and their renormalization is discussed. © 2010 Elsevier B.V.